Factors determining anti-malarial drug use in a peri-urban population from malaria holoendemic region of western kenya - Watsierah, Carren A (BioMed Central, 2010)
BACKGROUND: Interventions to reverse trends in malaria-related morbidity and mortality in Kenya focus on preventive strategies and drug efficacy. However, the pattern of use of anti-malarials in malaria-endemic populations, such as in western Kenya, is still poorly understood. It is critical to understand the patterns of anti-malarial drug use to ascertain that the currently applied new combination therapy to malaria treatment, will achieve sustained cure rates and protection against parasite resistance. Therefore, this cross-sectional study was designed to determine the patterns of use of anti-malarial drugs in households (n = 397) in peri-urban location of Manyatta-B sub-location in Kisumu in western Kenya. METHODS: Household factors, associated with the pattern of anti-malarials use, were evaluated. Using clusters, questionnaire was administered to a particular household member who had the most recent malaria episode (within <2 weeks) and used an anti-malarial for cure. Mothers/caretakers provided information for children aged <13 years. RESULTS: Stratification of the type of anti-malarial drugs taken revealed that 37.0% used sulphadoxine/pyrimethamine (SP), 32.0% artemisinin-based combined therapy (ACT), 11.1% anti-pyretics, 7.3% chloroquine (CQ), 7.1% quinine, 2.5% amodiaquine (AQ), while 3.0% used others which were perceived as anti-malarials (cough syrups and antibiotics). In a regression model, it was demonstrated that age (P = 0.050), household size (P = 0.047), household head (P = 0.049), household source of income (P = 0.015), monthly income (P = 0.020), duration of use (P = 0.029), dosage of drugs taken (P = 0.036), and source of drugs (P = 0.005) significantly influenced anti-malarial drug use. Overall, 38.8% of respondents used drugs as recommended by the Ministry of Health. CONCLUSION: This study demonstrates that consumers require access to correct and comprehensible information associated with use of drugs, including self-prescription. There is potential need by the Kenyan government to improve malaria care and decrease malaria-related morbidity and mortality by increasing drug affordability, ensuring that the recommended anti-malarial drugs are easily available in all government approved drug outlets and educates the local shopkeepers on the symptoms and appropriate treatment of malaria. Following a switch to ACT in national drug policy, education on awareness and behaviour change is recommended, since the efficacy of ACT alone is not sufficient to reduce morbidity and mortality due to malaria.